Autofluorescence as a Signal to Sort Developing Glandular Trichomes by Flow Cytometry - Bergau, Nick; Navarette Santos, Alexander; Henning, Anja; Balcke, Gerd U.; Tissier, Alain (Frontiers in Plant Science, 2016)
The industrial relevance of a number of metabolites produced in plant glandular trichomes has spurred research on these specialized organs for a number of years. Most of the research however, has focused on the elucidation of secondary metabolite pathways and comparatively little has been undertaken on the development and differentiation of glandular trichomes. One way to gain insight into these developmental processes is to generate stage-specific transcriptome and metabolome data. The difficulty for this resides in the isolation of early stages of development of the glandular trichomes. Here we describe a method for the separation and isolation of intact young and mature type VI trichomes from the wild tomato species Solanum habrochaites. The final and key step of the method uses cell sorting based on distinct autofluorescence signals of the young and mature trichomes. We demonstrate that sorting by flow cytometry allows recovering pure fractions of young and mature trichomes. Furthermore, we show that the sorted trichomes can be used for transcript and metabolite analyses. Because, many plant tissues or cells have distinct autofluorescence components, the principles of this method can be generally applicable for the isolation of specific cell types without prior labeling.